Infection Control Implementation At Private Dental Practice In Yogyakarta City - Dewanto, Iwan; Septario, Medi (Insisiva Dental Journal, 2012)
Dentist As A Health Worker Claimed To Be Responsible Widely In A Variety Of Existing Public Health Efforts, Especially In The Dental Clinic. Infection Control Is An Effort To Control And Prevent The Spread Of Infectious Diseases In Practice Setting. This Study Aimed To Describe The Implementation Of Infection Control In Dental Practices In The Yogyakarta City In The Availability And Utilization Of Facilities And Infrastructure. A CrossSectional Study Was Conducted In Yogyakarta City With Subjects Of 30 Dentist Who Has Independent Private Practice Chosen By Simple Random Sampling. Observational Techniques Using Check List Was Applied To Assess The Implementation Of Infection Control. Results Showed Existing Deficiencies Of Control Infection In The Components Of Equipment, Dentist, And Room. It Can Be Concluded That The Implementation Of Infection Control In The Yogyakarta City Has Not Gone Well, It Is Source Of Concern As The Possibility Of Infectious Disease Transmission In Dental Clinic Occured. This Because The Level Of Awareness Is Still Lacking And The Dentist Thinks Will Impact The Length Of The Culture Is Still Neglected